Value representation in political branding, why political party needed it? - Kaloka, Rintulebda Anggung; Larasati, Endang; Sardini, Nur Hidayat; Wijayanto, Wijayanto (Edelweiss Applied Science and Technology, 2025)
In an increasingly competitive political landscape, political branding plays a crucial role in shaping a party’s image and attracting voter support. This study explores the significance of value representation in political branding and why political parties need it to strengthen their identity and increase electability. Using a qualitative approach, this research analyzes how the values upheld by a political party influence public perception, foster voter loyalty, and differentiate the party from its competitors. This finding shows that the success of political imaging depends on how well the party’s values align with the cultural values embraced by society. These cultural values must be represented in the branding strategy. A strong and authentic value representation enhances credibility, trust, and appeal, making a political party more relevant and sustainable in a dynamic political environment. Therefore, a deep understanding of value representation is essential for building a compelling and long-lasting political brand.